Digital Image Analysis Tools Developed by the Indiana O’Brien Center - Dunn, Kenneth W. (Frontiers in Physiology, 2021)
The scale and complexity of images collected in biological microscopy have grown enormously over the past thirty years. The development and commercialization of multiphoton microscopy has promoted a renaissance of intravital microscopy, providing a window into cell biology in vivo. New methods of optical sectioning and tissue clearing now enable biologists to characterize entire organs at subcellular resolution. New methods of multiplexed imaging support simultaneous localization of forty or more probes at a time. Exploiting these exciting new techniques has increasingly required biomedical researchers to master procedures of image analysis that were once the specialized province of imaging experts. A primary goal of the Indiana O’Brien Center has been to develop robust and accessible image analysis tools for biomedical researchers. Here we describe biomedical image analysis software developed by the Indiana O’Brien Center over the past twenty-five years.